Nutritional value of grass mixture of birdsfoot trefoil with timothy grass depending on use modes - V. A. Figurin; N. P. Suntsova; A. P. Kislitsyna (Аграрная наука Евро-Северо-Востока, 2016)
Studying of modes of use of legume-grass mixture of birdsfoot trefoil with timothy grass was spent under conditions of the Kirov region at cultivation on strong acid soil. It is established that given grass mixture is energetically high-protein forage. The content of a crude protein in grass mixture depended on a part of trefoil in a yield, phases of development as well as on hay crops. The high content of protein in this mixture is noted in early phases of trefoil development (branching and budding) under favorable conditions of growth - in the first hay crop up to 14.5%, in the second hay crop increased up to 16.88% at a part of trefoil in a yield more than 50%. Under drought condition the content of a crude protein decreased as a rule especially in a flowering phase - to 9.09%. High concentration of exchange energy (more than 10 MDJ/kg of dry matter) is noted at cutting in all phases of trefoil development especially in the second and third hay crops. With passage of phases of plant development from branching till flowering the content of cellulose increased as a rule from 9…14 up to 21…26% in dependence on year of life and weather conditions. Herbages in early phases of development possess higher content of crude ashes and fat.